Two Newspaper Notes (Osservatore Dalmato) on the Find of the Inscription CIL III, 1745 from the Year 1856 (Archaeologia Adriatica, 2009)
In the third volume of the collection of Latin inscriptions Corpus inscriptionum Latinarum an inscription was published under the number 1745. It was written on a base of a monument which was set up in the first half of the 2nd century in honour of an Epidaurum notable P. Aelius Osillianus. The inscription was found in 1856, when two interesting articles about the find of that inscription in Cavtat were published in the Zadar newspaper Osservatore Dalmato (nos. 79 and 96). They were written by Mato Vodopić and Šime Ljubić. The author presents a transcript of the published articles (Appendix I and Appendix II) and comments on their contents, mentioning also basic biographical information about their authors. Mato Vodopić was a theologian, writer an natural scientist, who became a bishop of Dubrovnik by the end of his life (Fig. 1). Šime Ljubić was a writer, historian and an archaeologist, who is rightfully esteemed as one of the founders of modern archaeology in Croatia due to his self-sacrifying and above all professional work (Fig. 2). On the basis of epigraphic and onomastic analysis the author presents his own comment on the text of the inscription CIL III, 1745 (Fig. 3). P. Aelius Osillianus was an Epidaurum notable who probably originated from an autochtonous Romanized family from the colony territory or nearby inland. Namely, as his naming formula indicates, his family obtained citizenship during the Emperor Hadrian, and as early as the first half of the 2nd century it had risen significantly in the social scale band belonged to the highest aristocracy in Epidaurum. This is evident from the inscription text, since due to family's reputation, and his personal achievements, the entire city council honoured P. Aelius Osillianus and determined the place for raising the monument by unanimous vote. All activities regarding the construction of the monument and organizing accompanying ceremonies, which implied covering the costs as well, were managed by Ossilianus' mother Novia Bassila and grandmother Iustilla. When the monument was inaugurated, they gave appropriate gifts (sportulae), to the members of the city council, augustales and seviri, and for their fellow-citizens they organized boxing matches. The inscription CIL III, 1745 is exceptionally important since it documents almost entire procedure of paying respect to a deserving citizen during the first half of the 2nd century in Epidaurum.
Keywords: Osservatore Dalmato; Mato Vodopić; Šime Ljubić; Epidaurum; CIL III; 1745